An Approximate Solution Of Fredholm Integral Equation Of The First Kind By The Regularization Method With Parallel Computing - et. al., H.K. Al-Mahdawi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we study the regularization method for solving the Fredholm integral equation first kind. The discretization algorithm with two variables has applied to formulate the problem into a linear operator equation for the first kind. The parallel computing method has used to obtain the approximation solution by using a set of regularization parameters of the Tikhonov regularization method. The inverse initial value problem for the heat equation used as an example to test parallel computing and compared with sequential computing.